JAVANESE TRADITIONAL SETTLEMENTS TRANSFORMATION ON SEVERAL YOGYAKARTA TOURISM VILLAGSES - Bicawasti Budi Sutanty, Prisca
The research is based on a change in the orientation of an agrarian village to a tourist village that influences traditional Javanese settlements. Tourism villages prioritize cultural values with deep meaning and grip on the ancestral values of Javanese culture and customs. To respond to opportunities, residents make several adjustments to changes or transformations both at the home scale and environmental scale to meet the demands and needs of tourists. The purpose of this research is to find out the changes that occur at the indoor scale and the environmental scale. From the objectives which are quite broad in scope, a more in-depth discussion is needed by grouping the discussions based on the scope of the transformed area and the type of traditional house. So that the discussion of this study includes changes in function on a scale in traditional houses with the categories of residential homes and meeting houses; changes in the territory on a scale in the house during daily life (low season) and during tourism activities (peak season); as well as knowing changes on an environmental scale after becoming a tourist village during daily life (low season) and during tourism activities (peak season).